Muslim Prejudices in Bengal and Establishment of the University of Dhaka: A Study of Kazi Imdadul Haque’s Abdullah - Rahman, Mahabuba; Ahmed, Istiaque (Spectrum, 2022)
If we reflect on the history of the University of Dhaka, we come to know that it was not easy to establish the University. Battling with the dominance of the then Hindu political leaders, the Muslims of East Bengal finally achieved their long-cherished dream of educating themselves through a standard educational institution of their own. Kazi Imdadul Haque, one of the most prominent writers of Bangladesh, was a witness to those challenging times. His writings address history, politics, glorified past, and dreams of the future of Bengal. Abdullah, first published in 1932, his masterpiece, focuses on the educational stand of the Muslim community of Bengal before the Partition of the Indian subcontinent. The protagonist of the novel Abdullah mirrors the struggles of those who supported the establishment of the University of Dhaka. The obstacles he faces in order to educate and establish himself suggest the dire situation of the Muslims who were willing to work towards their betterment, but were helpless due to various pressures from the dominant community in power, and in many cases due to some prejudices of their own community. This paper, in light of the novel, addresses such issues and explores how the Muslims were able to break free of this vicious cycle of prejudice and ignorance through proper implementation of education. Spectrum, Volume 16, June 2021: 68-81